Muerte fetal: realidad en Chile entre 1995-2004 - Valdés R., Enrique; Preisler R., Jessica; Toledo M. , Verónica (Revista Hospital Clínico Universidad de Chile, 2008)
Objective: to know the late fetal mortality rate (LFMR) in Chile between 1995 and 2004. Methods: descriptive study analyzing the fetal deaths occurred in Chile in the period 1995-2004. Results: the LFMR in the period studied was 4,4 /1000newborns (NB). The LFMR in 2004 was 3.7/1000 NB and the most prevalent etiologies were: gestational pathologies (49%), ovular pathologies (21.7%), intrauterine hypoxia (12.8%), congenital malformations (6.5%), maternal pathology not related with pregnancy (4.2%) and undetermined cause (3.7%). Conclusions: The LFMR and the frequency of the etiologies of fetal deaths found in our study were important to plan the prevention strategies of perinathology.